2014
DOI: 10.1002/ange.201408246
|View full text |Cite
|
Sign up to set email alerts
|

Composite Aromatic Boxes for Enzymatic Transformations of Quaternary Ammonium Substrates

Abstract: Cation-p interactions to cognate ligands in enzymes have key roles in ligand binding and enzymatic catalysis. We have deciphered the key functional role of both charged and aromatic residues within the choline binding subsite of CTP:phosphocholine cytidylyltransferase and choline kinase from Plasmodium falciparum. Comparison of quaternary ammonium binding site structures revealed a general composite aromatic box pattern of enzyme recognition sites, well distinguished from the aromatic box recognition site of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
6
0
3
Order By: Relevance
“…We have also monitored the distance between the nitrogen and the carboxylate oxygens of a nearby aspartate residue (Asp623) (Fig.4B), as the experimental work suggested that it contributes to the binding of the ligand via electrostatic interactions. [14] What is quite apparent is that in the mutants the aspartate-choline distance has decreased which indicates the strengthening of their interaction. and the aspartate oxygens (B) during the MD simulations in the three enzyme variants.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have also monitored the distance between the nitrogen and the carboxylate oxygens of a nearby aspartate residue (Asp623) (Fig.4B), as the experimental work suggested that it contributes to the binding of the ligand via electrostatic interactions. [14] What is quite apparent is that in the mutants the aspartate-choline distance has decreased which indicates the strengthening of their interaction. and the aspartate oxygens (B) during the MD simulations in the three enzyme variants.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 97%
“…[12,13] Furthermore, detailed information exists on the role of the various active site side-chains on ligand binding affinity and enzyme activity, and detailed thermodynamic properties of point mutants, which will enable us to compare the computed results to experiments. [14] PfCCT functions as a homodimer ( Fig. 1) and plays a key role in the membrane synthesis of the pathogen of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Az ábrán a következõ színkóddal jelöltük a nem-kovalens kölcsönhatásokban résztvevõ csoportokat: apoláros kontaktusokban résztvevõ oldalláncok C-atomjai sárga színnel, míg a poláros vagy töltött kölcsönhatást biztosító oldalláncok C-atomjai kék színnel, a CDP-kolin ligandum C-atomjai zöld színnel láthatóak, a többi atom a szokásos atomi színkódnak megfelelõen vannak színezve (O: piros, N: kék, P: narancssárga). A CCT fehérje többi feltüntetett C-atomja szürke, továbbá az aktív centrum közeli fehérje-fõláncot (peptidvázat) szintén szürke szalagmodell mutatja 10 . A kutatásainkban felderített "composite aromatic box" általános karakterét a jobb alsó betétábra szemlélteti 10 .…”
Section: áBraunclassified
“…A CCT fehérje többi feltüntetett C-atomja szürke, továbbá az aktív centrum közeli fehérje-fõláncot (peptidvázat) szintén szürke szalagmodell mutatja 10 . A kutatásainkban felderített "composite aromatic box" általános karakterét a jobb alsó betétábra szemlélteti 10 .…”
Section: áBraunclassified
“…During these selective interactions a generally occurring natural phenomenon called molecular recognition plays a vital role. The complexes, formed by the host and guest molecules, are held together by secondary interactions, such as hydrogen bonding, π-π [3][4][5] and cation-π [6][7][8] interactions. Receptors based on various macrocycles, such as monensin [9], bispyrrolidone [10] and crown ether derivatives [11][12][13][14][15][16][17][18][19][20], were capable of selective recognition of sodium ions.…”
Section: Introductionmentioning
confidence: 99%